A Sociological Perspective on Drug Mishandling in Contemporary Sesotho Literature: An Analysis of Brian Makara’s Poem ‘Sethethefatsi’ - Soyiso Khetoa (E-Journal of Humanities, Arts and Social Sciences)
This study examines the social representation of drug abuse in Brian Makara’s poem “Sethethefatsi.” The prevalence of drug abuse among South African township youth has increased dramatically. This has resulted in the development of diverse intervention techniques at multiple levels across the country. In response to the drug endemic, literary writers like Makara use their art to raise awareness of this pervasive issue. This study argues that poetry serves as a valuable medium for exploring social phenomena because literature often reflects societal experiences. This study is underpinned by the theory of the sociology of literature, which views poetry as a reflection of society, social commentary, and the expression of a collective’s consciousness. This research adopts a desktop qualitative research approach to analyse how drugs are represented in Makara’s poem. The findings reveal that Makara personifies drugs for two reasons: (a) to portray drugs as an “individual” with harmful intentions infiltrating society; and (b) to depict drugs as a product of those who undermine societal values, whose intention is to obstruct societal development and sustainability. The study demonstrates that literary texts are valuable sources that engage with societal issues. Furthermore, the study signals that the contemporary Sesotho literature critically examines societal challenges that warrant political and policy interventions.